One ultramarathon, two cities: differences in social impact perceptions. Issue 4 (2nd October 2019) - Scholtz, Marco
ABSTRACT: To ensure the positive sentiment of residents towards sporting events, it is important to understand and manage the social impact perceptions generated by such events at the host destinations. The Comrades ultramarathon is a unique event which affects the residents of two cities at the same time, meaning that diversified social impact management approaches may be needed. The research revealed apparent differences in social impact perceptions among the two cities. Despite the Comrades, as it is colloquially termed, being a single event, diversified management approaches are therefore needed. This study furthermore reveals that the size and diversity of communities' economies might influence residents' social impact perceptions.